Cutaneous pilomatrical carcinosarcoma: a case report with molecular analysis and literature review - Thi My Hanh Luong; Yuko Akazawa; Zhanna Mussazhanova; Katsuya Matsuda; Nozomi Ueki; Shiro Miura; Toshihide Hara; Hiroko Yokoyama; Masahiro Nakashima (Diagnostic Pathology, 2020)
Abstract Background Cutaneous pilomatrical carcinosarcoma (CS) is a very rare biphasic tumor composed of admixed epithelial and mesenchymal malignant cells, with limited information on its pathogenesis. We report a case of pilomatrical CS of the scalp with comparative immunohistochemical and molecular analysis together with a review of the literature. Case presentation A 74-year-old woman presented with a rapidly growing long-standing tumor of the scalp. The tumor was surgically resected. Histologically, the tumor was 25 mm in diameter, and was composed of carcinoma showing a clear pilomatrical differentiation and sarcoma with pleomorphic spindle cells and giant cells. Both epithelial and mesenchymal components shared focal cytoplasmic and/or nuclear accumulation of β-catenin based on immunohistochemical analysis, although a mutation of exon 3 of the CTNNB1 gene was not detected. Fluorescence in situ hybridization analysis revealed gains of chromosomes 9p21, 3, and 7 in both the epithelial and sarcomatous components. Conclusions The current case demonstrated characteristic findings of pilomatricoma and further evidence of partial clonality between the carcinomatous and sarcomatous component, suggesting the possibility of malignant transformation of pilomatricoma. Rapid growth of a pilomatrical tumor should warrant the development of a malignant tumor, including CS.